The law of American state constitutions - Williams, Robert F. (Robert Forrest), 1945- (New York ; Oxford : Oxford University Press, 2009)
This book provides complete coverage of American State Constitutional Law, contrasting it with the more familiar federal Constitution and explaining the importance of the differences. It surveys the law from before adoption of the federal constitution until the present and studies how it has evolved.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Constitutional law -- United States -- States; Constitutions -- United States -- States